Exploring Gender Differences in Spatial Reasoning: Analyzing Hyperbolic Problem-Solving Skills Among University Students - Siti Suprihatiningsih; Rizki Kurniawan Rangkuti; Muhammad Firman Annur; Erwin Erwin; Irvan Irvan; Ebenezer Bonyah (Department of Mathematics Education Program IPI Garut, 2026)
Penelitian mengenai perbedaan penalaran spasial berdasarkan gender di tingkat universitas masih memerlukan konfirmasi lebih lanjut. Penelitian ini bertujuan mendeskripsikan perbedaan langkah-langkah penyelesaian soal hiperbola antara mahasiswa laki-laki dan perempuan. Menggunakan metode kualitatif, penelitian ini melibatkan 30 mahasiswa yang dipilih melalui rumus Slovin dari total populasi 480 mahasiswa. Instrumen penelitian meliputi tes soal hiperbola dan pedoman wawancara. Hasil penelitian menunjukkan adanya perbedaan signifikan pada aspek orientasi spasial, di mana mahasiswa perempuan menunjukkan keunggulan dalam langkah-langkah penyelesaian karena pemahaman konsep jarak yang lebih baik. Temuan ini menyimpulkan bahwa terdapat karakteristik unik pada penalaran spasial perempuan di tingkat pendidikan tinggi yang berbeda dari temuan umum di tingkat sekolah. Hasil penelitian ini memberikan kontribusi teoretis bagi pengembangan literatur penalaran spasial dalam pendidikan matematika. Research on gender-based differences in spatial reasoning at the university level requires further empirical confirmation. This study aims to describe the differences in procedural steps for solving hyperbola problems between male and female students. Employing a qualitative method, the study involved 30 students selected via Slovin’s formula from a population of 480. Research instruments consisted of hyperbola problem-solving tasks supported by interview transcripts. The findings reveal distinct differences in spatial orientation, where female students demonstrated superior performance in solving steps due to a robust understanding of distance concepts. In conclusion, these results highlight unique spatial reasoning characteristics among female students in higher education, diverging from common findings at the school level. This research contributes to the theoretical development of spatial reasoning literature within mathematics education.